2007
DOI: 10.1007/s12038-007-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation of a novel isoform of Na+/H+ antiporter from Pennisetum glaucum for enhancing salinity tolerance in rice

Abstract: Salt stress is an environmental factor that severely impairs plant growth and productivity. We have cloned a novel isoform of a vacuolar Na+/H+ antiporter from Pennisetum glaucum (PgNHX1) that contains 5 transmembrane domains in contrast to AtNHX1 and OsNHX1 which have 9 transmembrane domains. Recently we have shown that PgNHX1 could confer high level of salinity tolerance when overexpressed in Brassica juncea. Here,we report the functional validation of this antiporter in crop plant rice. Overexpression of Pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(41 citation statements)
references
References 38 publications
1
39
1
Order By: Relevance
“…The putative transgenic nature of the selected plants was confirmed using a second level of screening at the plant level using the leaf disc bioassay. Leaf disc bioassay is another reliable tool for the screening of plants under specific stress (SinglaPareek et al 2003(SinglaPareek et al , 2006Verslues et al 2006;Verma et al 2007). The tolerant plants selected after screening at seedling level were subjected to leaf disc bioassay by using leaf bits from 60-day old plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative transgenic nature of the selected plants was confirmed using a second level of screening at the plant level using the leaf disc bioassay. Leaf disc bioassay is another reliable tool for the screening of plants under specific stress (SinglaPareek et al 2003(SinglaPareek et al , 2006Verslues et al 2006;Verma et al 2007). The tolerant plants selected after screening at seedling level were subjected to leaf disc bioassay by using leaf bits from 60-day old plants.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf discs of 1 cm bits (5 No.) were finely cut from the upper half of the leaf and floated on a 20 mL solution of CdCl2 (75, 100 and 125 µM, 72 h); sterile distilled water served as experimental control (Fan et al 1997;Verma et al 2007). The effect of Cd stress treatment on leaf segments was assessed by scoring for chlorosis.…”
Section: Transformation and Development Of Transformantsmentioning
confidence: 99%
“…Genes imparting to salinity tolerance in crop plants have been widely characterized, especially, those are involved in transcription, transduction, transportation of ion and metabolic (Verma et al, 2007;Singh et al, 2007;Kumari et al, 2009). Few studies have revealed the metabolic influence of salinity on crop plants such as grape vine, rice, tomato, and Arabidopsis (Gong et al, 2005).…”
Section: Salt Stress Tolerance and Plant Metabolismmentioning
confidence: 99%
“…These 1005 lines, at the three true leaf growth stage, growing in the National Chung Hsing University glasshouse were treated with 150 mM NaCl for three weeks. According to the procedure of Verma et al (2007), 11 salt-tolerant lines were selected, grown and developed to the seventh generation. All 13 lines, including the 11 selected lines, CNY911303, and TNG67 seedlings with six true leaves, were treated with 300 mM NaCl for three days after (Ohta et al, 2002).…”
Section: Plant Materialsmentioning
confidence: 99%